The Effect of Fast Food Consumption on Adolescent Health: A Literature Review - Firayani, Firayani (Pt. Anagata Sembagi Education, 2024)
The shift in adolescent consumption patterns towards fast food dominance has become a complex global issue, especially in developing countries like Indonesia. Fast food is now not only a practical choice, but also a symbol of modernity and lifestyle that is massively promoted by digital media. This study aims to examine the impact of fast food consumption on adolescent physical and psychosocial health through a qualitative approach with a literature study method. Data were collected from various accredited scientific sources, including international journals, health organization reports, and relevant national survey results, with a publication period of the last five years (2019–2024). The findings show that excessive consumption of fast food is strongly correlated with an increase in the prevalence of obesity, metabolic syndrome, and psychological disorders such as negative body image and stress. Low nutritional literacy, minimal formal education, and the dominance of unhealthy food promotions on social media exacerbate adolescent vulnerability to the long-term impacts of such consumption. Therefore, multidimensional interventions are needed that not only target individual consumption behavior but also reform information systems, educational curricula, and regulations on fast food marketing to adolescents. This study emphasizes the importance of scientific literature as a basis for evidence-based adolescent health policies.